Enhancement of docosahexaenoic acid synthesis by manipulation of antioxidant capacity and prevention of oxidative damage in Schizochytrium sp. (January 2017) - Ren, Lu-Jing; Sun, Xiao-Man; Ji, Xiao-Jun; Chen, Sheng-Lan; Guo, Dong-Sheng; Huang, He
Highlights: A new control strategy by manipulating antioxidant capacity was proposed. Ascorbic acid enhances cellular antioxidant capacity to resist oxidative injury. ROS decreased by 35.5% and T-AOC kept above zero until the end of fermentation. Ascorbic acid increased PUFA content with specificity improvement in DHA content. DHA yield was increased by 44% by two-point ascorbic acid addition strategy. Abstract: Oxygen-mediated cell damage is an important issue in aerobic fermentation. In order to counteract these problems, effect of ascorbic acid on cell growth and docosahexaenoic acid (DHA) production was investigated in Schizochytrium sp. Addition of 9 g/L ascorbic acid resulted in 16.16% and 30.44% improvement in cell dry weight (CDW) and DHA yield, respectively. Moreover, the total antioxidant capacity (T-AOC) of cells decreased from 2.17 at 12 h to 0 at 60 h and did not recover, while ascorbic acid addition could extend the time of arrival zero with the reduced intracellular ROS. However, ROS levels still increased after 72 h. Therefore, to further solve the problem of high ROS levels and low T-AOC of cells after 72 h, a two-point addition strategy was proposed. With this strategy, DHA yield was further increased to 38.26 g/L. This work innovatively investigated the feasibility of manipulating Schizochytrium sp. cultivation through ROS level and T-AOC.